Parental Position towards Adult Children: Development and Approbation of Method - Egorov R.N.; Shapovalenko I.V. (Психолого-педагогические исследования)
The article is devoted to the development of the author’s methodology for determining the parental position in relation to adult children. The creation of the questionnaire was one of the main objectives of the study, aimed at identifying and describing various types of parental position in relation to adult children. At the main stage of the work, 167 parents (mothers and fathers) of children aged 18 to 30 were interviewed. In the course of the study, the statistical analysis of the method using the exploratory and confirmatory factor analysis was carried out, the checking of the internal consistency of the scales, its retest reliability and validation. As a result, the structure of the questionnaire was clarified and a conclusion was drawn on its applicability for research purposes. During the study, the main factors that determine the nature of the relationship between parents and adult children (“adoption” and “control”) have been established, on the basis of which 4 types of parental position in relation to adult children have been empirically identified: autonomous, detached, controlling, balanced.